Innovating the perception on pawning: An integrated marketing communications campaign for Villarica pawnshop - Sacilioc, Joses M. (Animo Repository, 2017)
As mankind's oldest financial institution, pawnbroking carries on a tradition with a rich history. Pawnbroking can be traced back at least 3,000 years to ancient China, and has been found in the earliest written histories of Greek and Roman civilizations. (Wordpress.com,2017) In fact, statutory regulations of banking and finance are based on the legal foundation established by leaders in the banking industry. This system had its roots in pawnbroking. Since 3,000 years ago, pawnshops continue to be a source of convenient credit for individuals in need of a short-term loan. 3000 years later, 2016 was another great year for consumer lending in the Philippines, which recorded double digit growth. The domestic economic condition showed moderate growth with political stability thanks to the presidential election in the first half of 2016. Consumers have more confidence in taking auto, card, home, education and other personal loans. Retail banks have promoted heavily to acquire new borrowers, in particular of auto loans, and huge demand for card lending. The government plays an important role in promoting education loans for which the three key providers are the Government Service Insurance System (GSIS), the Social Security System of the Republic of the Philippines (SSS) and the stated owned Development Bank of the Philippines (DBP). (Euromonitor, 2016. Despite the growth in the consumer lending category, the data says that the drivers for growth are long-term loans like cars, education and mortgage. Only credit cards are formally addressing short-term loans and there is a lot of work to do given the low credit card penetration in the Philippines. In the context of jewelry, despite having fewer Filipino consumers who use jewelry as an investment, the jewelry category still saw healthier growth in 2016. This means that the low penetration of credit cards, and the rising jewelry category growth makes up for a huge opportunity for pawning. This paper is an integrated marketing communications campaign for Villarica Pawnshop, one of the market leaders in the pawning industry in the Philippines. This will discuss how we can further increase market share for the brand. There are other services that are offered by Villarica and its competitors, but the focus will only be on the pawning service. The IMC campaign latches on the insight where one experiences difficulty when borrowing money from friends or relatives especially if the person is a non-credit card owner.